Rh-catalyzed synthesis of coumarin derivatives from phenolic acetates and acrylates via C-H bond activation - Gadakh, Sunita K.; Dey, Soumen; Sudalai, Arumugarn (Journal of Organic Chemistry, 2015)
An efficient annulation strategy involving the reaction of phenolic acetates with acrylates in the presence of [Rh-2(OAc)(4)] as catalyst and formic acid as reducing agent, leading to the high yield synthesis of coumarin derivatives, has been developed. The addition of NaOAc as a base increased the yield of the products. The reaction is quite Successful for both electron rich as well as electron deficient phenolic acetates, affording coumarins with excellent regioselectivity, and proceeds via, C-H bond activation proven by deuterium incorporation studies.